Geoscience of Climate and Energy 10. The Alberta Oil Sands: Developing a New Regime of Environmental Management, 2010–2013 - Miall, Andrew D. (Geoscience Canada, 2013)
DOI: http://dx.doi.org/10.12789/geocanj.2013.40.015